POTENSI KANDUNGAN PIGMEN KLOROFIL a DAN b BEBERAPA RUMPUT LAUT GENUS Gracilaria: OPTIMALISASI KANDUNGAN KARBOHIDRAT - Dewi, Rose; Nugrayani, Dewi; Sanjayasari, Dyahruri; Endrawati, Hadi (Jurnal Harpodon Borneo, 2016)
Response pigment and ecological is major factor of photosynthesis. Quantity of chlorophyll a,b are not same in Gracilaria, though in one genus. Difference fluctuation ecological conditions on waters; (Station 1): estuaries, (Station 2): coastal, (Station 3): 100m from the shoreline, based on literature study will affect the rate of  photosynthesis. This research aims  need to measure of quantitatively pigments (chlorophyll a,b) and carbohydrate to know the difference. Method by purposive random sampling; chlorophyll a,b using UV-Vis spectrophotometer; carbohydrate with analysis by difference; also control  physical and chemical parameters of waters. Results show the chlorophyll a, b and carbohydrates in G. verrucosa (163.58 ± 8.90mg /L;79.32 ± 5.53 mg /L; 37.19 ± 1.50%); G. gigas (128.01 ± 7.2 mg /L;117.76 ± 5,85mg /L; 44.48 ± 0.90% ) and G. salicornia (100.36 ± 23.35mg/L; 93.73 ± 11,59mg/L; 36.94 ± 0.72%). The highest correlation between pigments (chlorophyll b) with the formation of carbohydrate in G. gigas (r = 0.991). Range of water quality measured during the study still the threshold that can be tolerated Gracilaria, found only high phosphorus content above the threshold that 1.935 to 2.517 mg/ L.Key words: G. verrucosa, G. gigas, G. salicornia, Chlorophyll a, b , Carbohydrate